(3GdQSGdI GdTeSjI aj GdbhGYO GdefWbjIs - (3GdcGJHj GdbRhjfj, fLe GdOjf, OHjQGf, Ydj Hf YeQ Hf Ydj, (B675 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj CHOY fXGe GdhLhO (B... (3agPG GdcJGH eTJed GdbhGYO hSejJg hQJHJg Ydi ebOeI hKdGK ebGdGJ hNGJeI eYJUeG HMHd GdJhajb ef hGgH GdYbd heJhcdG Ydi hLhOg GdeajV ddNjQ hGdYOd (B...s
(3BNQgG (B:s
(3cbhdfG cd ebOGQ hSW aj GdfSHI agh VdY HGdMjW Hg GdWQaGf hbO jchf fhYg cbhdfG cd NjW jecf JfUjag hbO jchf fhYg eY YQV PGJj cbhdfG cd NW bGe Ydi BNQ aEf RGhjJj LfHjg (B... (3Jes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4\315s
(3cTa GdXfhf (B2\1063s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdadSaI hGdefWbs